2008
DOI: 10.1007/s10775-008-9149-5
|View full text |Cite
|
Sign up to set email alerts
|

Residing in silence and wonder: career counselling from the perspective of ‘being’

Abstract: We are approaching career counselling from the perspective of ''Being'', which we recognize to be a daunting task. Nevertheless we find it extremely important that the counsellor become aware of and try to think, talk and act from his or her embeddedness in being, and by that help the client to do the same. This process involves an ontological and spiritual approach, and builds upon the Socratic ability to wonder, the meditative way of ''undoing'' and the artful act of creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…Just be there.'' The value of presence is one of the main factors in the studies by Hansen and Amundson (2009) and Ribner and Knei-Paz (2002). The findings of the present study portray clearly that from the participants' perspective a good professional must be respectful, professional, caring, sincere, and humane.…”
Section: The Need To Feel Cared For and Counseledsupporting
confidence: 54%
See 2 more Smart Citations
“…Just be there.'' The value of presence is one of the main factors in the studies by Hansen and Amundson (2009) and Ribner and Knei-Paz (2002). The findings of the present study portray clearly that from the participants' perspective a good professional must be respectful, professional, caring, sincere, and humane.…”
Section: The Need To Feel Cared For and Counseledsupporting
confidence: 54%
“…Manthei's (2007) study reflects well the importance of talking and listening. A teamwork study by Hansen and Amundson (2009) about counseling and Smithson, Hukins, and Jones's (2006) study showed similar results.…”
Section: Rehabilitation Solutions and Opportunitiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Vi kan ikke fange eller kontrollere eksistensielle øyeblikk ved hjelp av en metode. Slike øyeblikk er noe vi kan motta når vi er i undring: stille, forsiktig og oppmerksomt til stede (Gadamer, 2010;Hansen & Amundson, 2009). Undring var det framtredende aspektet ved min rolle som moderator i fokusgruppa.…”
Section: Om Undring Og Undringskvaliteterunclassified
“…Conceptions, requirements, relations between theory and practice regarding the competences and training of career practitioners have been refl ected from diff erent angles in many studies of researchers like Brown & Krane (2000), Hansen (2001;, Plant (2001;, Inglar, Bjerknes, Lappen, and Tobiassen (2003), Bimrose (2004), McCarthy (2004), Borgen & Hiebert (2006), McMahon & Patton (2006), Schon (2007), Arthur (2008), Repetto (2008), Reid (2003;2015), Reid & West (2011a;2011b), Schiersmann (2008), Hansen & Amundson (2009), Hiebert (2009), Savickas, Nota, Rossier, Dauwalder, Duarte, Guichard, Soresi, Van Esbroeck, and van Vianen (2009, Pukelis and Navickiene (2011), Savickas (2005;2011b;2013), Sultana (2003;, Sultana & Watts (2006), Watts & Sultana (2004), etc. Th e aim of this paper is to share the experiences accumulated in the European pro jects NICE and NICE 2 increasing professionalization of career services and working towards excellence and innovation in the academic training of career practitioners. Th e focus of this paper is to present a theoretical framework (methodology) for defi ning competences of BA, MA and PhD cycle degree programmes for the academic training of career (2012)(2013)(2014)(2015), based on a prior mo del developed in NICE (2009NICE ( -2012 4 .…”
Section: Kęstutis Pukelis Johannes Katsarov Karjeros Paslaugų Teikėjmentioning
confidence: 99%